Determinants of Oral Complications Among Diabetes Mellitus Patients at Industri Health Center - Puspani, Desak Ketut Mahayati Tri; Wahyuningsih, Atik Setiawan; Astutik, Reni Yuli (KHD Production, 2026)
Diabetes mellitus (DM) increases patients’ susceptibility to various oral complications, including dental caries, periodontal disease, xerostomia, and oral candidiasis. This study aimed to examine the influence of demographic, clinical, behavioral, and oral health knowledge factors on the occurrence of oral complications among patients with DM, and to assess the potential mediating role of the Oral Hygiene Index-Simplified (OHI-S). An analytical observational study with a cross-sectional design was conducted involving 90 patients with DM selected through purposive sampling. Data analysis included Chi-square tests to assess bivariate associations (X→Y), Ordinary Least Squares (OLS) regression to evaluate the effects of independent variables on OHI-S scores (X→M), multivariate logistic regression to examine the association between OHI-S and oral complications (M→Y), and mediation analysis using OLS regression pathways. Most participants presented with moderate oral complications (54.44%), followed by mild (26.67%) and severe (18.89%) categories. Bivariate analysis revealed significant associations between oral health knowledge (χ² = 43.445; p < 0.001) and type of DM (χ² = 7.282; p = 0.026) with oral complications. OLS regression demonstrated that only oral health knowledge significantly influenced OHI-S scores (β = −0.392; p < 0.001). However, multivariate logistic regression indicated that OHI-S was not a significant predictor of oral complications (β = 0.0139; p = 0.957; OR = 1.014; 95% CI: 0.61–1.68). Furthermore, mediation analysis showed no significant indirect effects (all p > 0.95), indicating that OHI-S did not mediate the relationship between the studied determinants and oral complications. Oral complications among patients with DM in primary healthcare settings are multifactorial. While oral health knowledge and DM type were significant determinants at the bivariate level, OHI-S did not function as a significant predictor or mediator in the multivariate model.